Community Based Tourism Development Strategy Of Cemagi Beach, Mengwi District, Badung Regency, Bali - Suastini, Ni Kadek; Dewi, Nyoman Diah Utari; Rai, Anak Agung Gede (Jurnal Scientia, 2024)
In developing community-based tourism at Cemagi Beach, the Government always includes the community in decision making. Second, management of coastal tourist attractions provides direct and indirect benefits to the community. The community can directly feel the economic increase from beach tourism activities. Indirectly, the large number of visitors who come to beach tourism locations can see and introduce themselves to the customs and customs of the local community. Third, involve managers, government and the community regarding good development procedures. Fourth, the government always provides space for the community to maintain its culture. Then the factors that support the development of community-based tourism are natural beauty that is still preserved and also free tourist locations. Then the inhibiting factors are the lack of public awareness in maintaining environmental cleanliness and the absence of regulations governing it.